PENGARUH LATIHAN DRIBBLING ZIG-ZAG DAN SLALOM DRIBBLE TERHADAP KETERAMPILAN DRIBBLING PEMAIN SSB PUTRA LINTAS BUNGO USIA 10-12 TAHUN - Deka Ismi Mori Saputra; Deddy Rahmat Saputra; Subhanadri Subhanadri (Jurnal Muara Olahraga, 2022)
Abstract The problem in this study is the lack of dribbling ability of SSB Putra Lintas Bungo player aged 10-12 years. This study aims to examine the dribbling ability of SSB Putra Lintas Bungo soccer players aged 10-12 years. This research is an experimental research. The technique used in the sample selection is purposive development phases. After doing the pre-tesst, all samples were divided into 2 groups through matched ordinal pairing technique. The results of the pre-test and post-test that were recorded were the length of time each testee got after doing the dribbling ability test. The data analysis technique used t-test with a significant level of =0.05. The results of the study are (1). There is an affect of zig-zag dribbling practice on the dribbling ability of SSB Putra Lintas Bungo players aged 10-12 years. With tcount 6.08 while ttable is 1.94 with a significant level of =0.05 and n = 7, then tcount > ttable (6.08 > 1.94). (2). There is an effect of slalom dribble training on the dribbling ability of SSB Putra Lintas Bungo players aged 10-12 years.with a tcount of 3.65 while t-table is 1.94 with a significant level of =0.05 and n = 7, then tcount > ttable (3.65 > 1.94). (3). There is a significant difference between the results of zig- zag dribbling training and slalom dribbling training on the dribbling ability of SSB Putra Lintas Bungo players aged 10-12 years. With tcount 2.92 while ttable 1.94 with a significant level of =0.05 and n = 7, then tcount > ttable (2.92 > 1.94). Thus, this value indicates that the given zig- zag dribbling and slalom dribble exercises have differences in improving the dribbling ability of SSB Putra Lintas Bungo players aged 10-12 years. Keywords: zig-zag dribbling practice, slalom dribble practice, dribbling ability